Relative age effect in youth soccer: analysis of the FIFA U17 World Cup competition - Williams, J. H. (Scandinavian Journal of Medicine & Science in Sports, 2010)
This investigation sought to determine if a relative age effect exists in the FIFA U17 World Cup competition. Birthdates of players competing in the most recent six competitions, from 1997 to 2007 were examined. For all competitions, the distributions of birth months were significantly different than expected with more players born in the early months of the year compared with the later months. For the entire cohort of players, 40% were born in the first quarter of the year while only 16% were born in the last 3 months. A small portion of this effect seems to be due to physical stature of the players. This relative age effect held for all FIFA-designated geographical zones except for Africa. The African region displayed a reverse relative age effect with a relatively large portion of players born in the later part of the year, particularly in December of the age appropriate year. The results of this investigation show that at the highest level of youth soccer, there is a strong bias toward inclusion of players born early in the selection year.